Defining the evolving field of culinary medicine across multiple domains - Hildebrand, Caitlin A.; Artz, Kristi E.; Dollinger, Beth; Dotson, Kerri; Dungan, David D.; Falquier, Sabrina A.; Faris, Basma; Fitzgerald, Nurgul; Guggenmos, Karl J.; Harlan, Gregory A.; Harlan, Timothy S.; Joseph, Karen E.; et al. (Frontiers in Nutrition, 2025)
Culinary medicine is an evolving field that spans multiple professions and settings. Prior definitions of culinary medicine may not reflect the expansion of this discipline or the variety of key stakeholders engaged in culinary medicine. To address the need for an updated definition of what culinary medicine means, a working group consisting of a variety of roles and professional/community settings was assembled to reach a consensus definition that is reflective of the current landscape of culinary medicine. Definitions that are tailored to the variety of stakeholders participating in culinary medicine are beneficial to engagement within and across professions in support of programming, clinical care, and access to healthy food with the ultimate goal of empowering patients/consumers to make healthier food choices.